Cardiovascular biomarkers predict post‐discharge re‐hospitalization risk and mortality among Swedish heart failure patients. (24th July 2019) - Molvin, John; Jujic, Amra; Bachus, Erasmus; Gallo, Widet; Tasevska‐Dinevska, Gordana; Holm, Hannes; Melander, Olle; Fedorowski, Artur; Magnusson, Martin
Abstract : Aim: The aim of this study was to assess the predictive role of biomarkers, associated with cardiovascular stress and its neuroendocrine response as well as renal function, in relation to mortality and risk of re‐hospitalization among consecutive patients admitted because of heart failure (HF). Methods and results: A total of 286 patients (mean age, 75 years; 29% women) hospitalized for newly diagnosed or exacerbated HF were analysed. Associations between circulating levels of mid‐regional pro‐adrenomedullin (MR‐proADM), copeptin, C‐terminal pro‐endothelin‐1, N‐terminal pro‐brain natriuretic peptide (NT‐proBNP), cystatin C, and all‐cause mortality as well as risk of re‐hospitalization due to cardiac causes were assessed using multivariable Cox regression models. A two‐sided Bonferroni‐corrected P ‐value of 0.05/5 = 0.010 was considered statistically significant. All biomarkers were related to echocardiographic measurements of cardiac dimensions and function. A total of 57 patients died (median follow‐up time, 17 months). In the multivariable‐adjusted Cox regression analyses, all biomarkers, except C‐terminal pro‐endothelin‐1, were significantly associated with increased mortality: NT‐proBNP [hazard ratio (HR) 1.85, 95% confidence interval (CI) 1.17–2.17; P = 4.0 × 10 −4 ], MR‐proADM (HR 1.94, 95% CI 1.36–2.75; P = 2.2 × 10 −4 ), copeptin (HR 1.70, 95% CI 1.22–2.36; P = 0.002), and cystatin C (HR 2.11, 95% CI 1.56–2.86; P = 1.0 × 10 −6 ). A total of 90 patients were re‐hospitalized (median time to re‐hospitalization, 5 months). In multivariable Cox regression analyses, NT‐proBNP was the only biomarker that showed significant association with risk of re‐hospitalization due to cardiac causes (HR 1.43, 95% CI 1.10–1.87; P = 0.009). Conclusions: Among patients hospitalized for HF, elevated plasma levels of NT‐proBNP, MR‐proADM, copeptin, and cystatin C are associated with higher mortality after discharge, whereas NT‐proBNP is the only biomarker that predicts the risk of re‐hospitalization due to cardiac causes.